IDO and Kynurenine Metabolites in Peripheral and CNS Disorders - Huang, Yi-Shu; Ogbechi, Joy; Clanchy, Felix I.; Williams, Richard O.; Stone, Trevor W. (Frontiers in Immunology, 2020)
The importance of the kynurenine pathway in normal immune system function has led to an appreciation of its possible contribution to autoimmune disorders such as rheumatoid arthritis. Indoleamine-2,3-dioxygenase (IDO) activity exerts a protective function, limiting the severity of experimental arthritis, whereas deletion or inhibition exacerbates the symptoms. Other chronic disorder with an inflammatory component, such as atherosclerosis, are also suppressed by IDO activity. It is suggested that this overall anti-inflammatory activity is mediated by a change in the relative production or activity of Th17 and regulatory T cell populations. Kynurenines may play an anti-inflammatory role also in CNS disorders such as Huntington’s disease, Alzheimer's disease and multiple sclerosis, in which signs of inflammation and neurodegeneration are involved. The possibility is discussed that in Huntington’s disease kynurenines interact with other anti-inflammatory molecules such as Human Lymphocyte Antigen-G which may be relevant in other disorders. Kynurenine involvement may account for the protection afforded to animals with cerebral malaria and trypanosomiasis when they are treated with an inhibitor of kynurenine-3-monoxygenase (KMO). There is some evidence that changes in IL-10 may contribute to this protection and the relationship between kynurenines and IL-10 in arthritis and other inflammatory conditions should be explored. In addition, metabolites of kynurenine downstream of KMO, such as anthranilic acid and 3-hydroxy-anthranilic acid can influence inflammation, and the ratio of these compounds is a valuable biomarker of inflammatory status although the underlying molecular mechanisms of the changes require clarification. Hence it is essential that more effort be expended to identify their sites of action as potential targets for drug development. Finally, we discuss increasing awareness of the epigenetic regulation of IDO, for example by DNA methylation, a phenomenon which may explain differences between individuals in their susceptibility to arthritis and other inflammatory disorders.